2012
DOI: 10.11606/issn.1806-6976.v8i1p17-24
|View full text |Cite
|
Sign up to set email alerts
|

O Papel do enfermeiro na adesão ao tratamento de pessoas com transtorno afetivo bipolar: o que os registros dizem?

Abstract: Trata-se de estudo descritivo-exploratório que descreve o papel do enfermeiro na adesão ao tratamento da pessoa com transtorno afetivo bipolar (TAB), através do levantamento de registros feitos por estudantes e enfermeiras nos prontuários, e aplicação de uma escala em um serviço comunitário de saúde mental. Utilizou-se a metodologia clínicoqualitativa e, como instrumento de coleta, um diário de campo. A escala foi aplicada no primeiro e último contato com cinco sujeitos do interior paranaense, no período de um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 16 publications
0
5
0
5
Order By: Relevance
“…Thus, one of the studies analyzed showed that the nurse in a care home, a communitybased service, used the NP in the treatment of one of the residents with a long-standing mental disorder, resulting in an improvement in the clinical status (14) , in this way, in the context of psychiatric nursing care, the focus of the NP is aimed a goals and based on a decision-making or problem resolving model that aims to improve patients' response to health problems and, in the patient in question, the goal was to better deal with their psychological suffering (5,14,28) . Another aspect to be considered in caring for patients with mental illness is adherence to treatment, defined as the degree to which patients adopt the health care professional's recommendations (6) , s two of the studies indicated that applying Irving's NP enabled two patients with mental disorders to adhere to treatment (15,19) , as it strengthened the treatment relationship between the nurse and the patient through developing the stages of the NP together, the linked between the subject and the nursing professional grew much closer (5) . At the same time, the NO contributes to constructing the treatment project as it enables the subjects' needs and responses to the health problems to be known, encouraging the drawing up of an individualized nursing care plan (5) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, one of the studies analyzed showed that the nurse in a care home, a communitybased service, used the NP in the treatment of one of the residents with a long-standing mental disorder, resulting in an improvement in the clinical status (14) , in this way, in the context of psychiatric nursing care, the focus of the NP is aimed a goals and based on a decision-making or problem resolving model that aims to improve patients' response to health problems and, in the patient in question, the goal was to better deal with their psychological suffering (5,14,28) . Another aspect to be considered in caring for patients with mental illness is adherence to treatment, defined as the degree to which patients adopt the health care professional's recommendations (6) , s two of the studies indicated that applying Irving's NP enabled two patients with mental disorders to adhere to treatment (15,19) , as it strengthened the treatment relationship between the nurse and the patient through developing the stages of the NP together, the linked between the subject and the nursing professional grew much closer (5) . At the same time, the NO contributes to constructing the treatment project as it enables the subjects' needs and responses to the health problems to be known, encouraging the drawing up of an individualized nursing care plan (5) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the studies show that a formal record of applying the NP was made, summarizing the data collected about the patient and their family, as well as interaction with the collective, at a specific moment in the subject's health-illness process, which will serve to guide the patient's treatment as well as proving the NP has been carried out (6) . Another of the studies portrayed the issue of identifying nursing phenomena identified in articles in journals on nursing care for adults admitted to psychiatric wards, concluding that in psychiatric nursing care, it is necessary to name and record the patients' problems and causes/related factors and triggers, as well as signs and symptoms (20) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations